2022
DOI: 10.3389/fimmu.2022.956533
|View full text |Cite
|
Sign up to set email alerts
|

The association between antibiotic use and outcomes of HCC patients treated with immune checkpoint inhibitors

Abstract: ObjectiveRecently, immune checkpoint inhibitor (ICI) treatment has shown encouraging performance in improving the prognosis of hepatocellular carcinoma (HCC) patients. The gut microbiome plays a vital role in altering the efficacy of ICIs, which may be impacted by antibiotics. The aim of the meta-analysis is to estimate the influence of antibiotic use on the survival of HCC patients treated with ICIs.MethodsThe literature review was conducted using databases like PubMed, EMBASE, Cochrane Library, CNKI, WANFANG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…confirmed the reliability and the robustness of the results, and which is in accordance with the meta-analyses previously published on the subject (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Exclusion of cohorts not having performed multivariate analyses further showed that this suggested deleterious impact persisted despite adjustment for confounding factors, suggesting that ABX use is an independent predictor factor for OS and PFS.…”
Section: Figure 11supporting
confidence: 89%
See 2 more Smart Citations
“…confirmed the reliability and the robustness of the results, and which is in accordance with the meta-analyses previously published on the subject (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Exclusion of cohorts not having performed multivariate analyses further showed that this suggested deleterious impact persisted despite adjustment for confounding factors, suggesting that ABX use is an independent predictor factor for OS and PFS.…”
Section: Figure 11supporting
confidence: 89%
“…With the increasing use of immune checkpoint inhibitors in cancer care, considerable efforts have been made to identify factors that may alter their effectiveness, and ABX use has recently emerged as one of them, as demonstrated by numerous retrospective and prospective studies (7,(12)(13)(14) and several meta-analyses (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) published on the topic. Our meta-analysis stands out from the others in that it included more than three-fold the number of Forest plot of odds ratios of the progressive disease rate of patients diagnosed with cancer and exposed to antibiotics versus not exposed to antibiotics around immune checkpoint inhibitor treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36,37] By checking the immune characteristics of HCC patients, that is the molecular and cellular characterization of TIME, individualized risk stratification of HCC patients can be achieved, and patients with significant therapeutic effects on immunotherapy can be identified, thereby guiding clinical decision-making and realizing the purpose of precise treatment. [38–40] In the present study, our 6-lncRNA panel demonstrated excellent stratification ability for immune infiltrating cells such as natural regulatory T cells, B cells, follicular helper T cells, mucosal-associated invariant T, macrophages and NK cells from HCC patients. These immune-infiltrating cells have all been found to be biomarkers for the prognosis of HCC, [41–47] which was of great significance for further research on the immune mechanism of HCC and the development of new diagnostic and therapeutic approaches.…”
Section: Discussionmentioning
confidence: 61%
“…Antibiotic treatment also decreases intestinal LPS overload [ 157 ]; in murine models of colitis-associated CRC, antibiotics and the TLR-4-blocking molecule Resatorvid [ 158 ] are able to inhibit inflammation, decreasing TLR-4 signaling and TLR-4+ tumor-infiltrating macrophages [ 159 ]. However, in a mouse model of methionine/choline-diet-induced NASH, antibiotics administration was reported to have negative effects [ 160 ], and a negative impact on HCC immunotherapy is described in different studies [ 161 , 162 , 163 ], so further evidence is needed to elucidate the role of antibiotics in gut microbiota modulation and tumor development. TLR-4 inhibition of host anti-tumor activity is also controversial, because, if it is true that tumor progression involves TLR-4-mediated production of pro-inflammatory and immunosuppressive cytokines, TLR-4 antagonists reduce pro-inflammatory response, but also compromise host immunity [ 164 ].…”
Section: Blocking Lps/tlr-4/m2 Cascade: Therapeutic Approachesmentioning
confidence: 99%